NUMB suppression by miR-9-5P enhances CD44+ prostate cancer stem cell growth and metastasis - Xuan Wang (Nature Portfolio, 2021)
Abstract Experimental and clinical studies over the past two decades have provided overwhelming evidence that human cancers, including prostate cancer (PCa), harbor cancer stem cells (CSCs) that sustain tumor growth, drive tumor progression and mediate therapy resistance and tumor relapse. Recent studies have also implicated NUMB as a PCa suppressor and an inhibitor of PCa stem cells (PCSCs); however, exactly how NUMB functions in these contexts remains unclear. Here, by employing bioinformatics analysis and luciferase assays and by conducting rescue experiments, we first show that NUMB is directly targeted by microRNA-9-5p (miR-9-5p), an oncogenic miR associated with poor prognosis in many malignancies. We further show that miR-9-5p levels are inversely correlated with NUMB expression in CD44+ PCSCs. miR-9-5p reduced NUMB expression and inhibited numerous PCSC properties including proliferation, migration, invasion as well as self-renewal. Strikingly, overexpression of NUMB in CD44+ PCSCs overcame all of the above PCSC properties enforced by miR-9-5p. Taken together, our results suggest that inhibiting the expression of the oncomiR miR-9-5p and overexpressing NUMB may represent novel therapeutic strategies to target PCSCs and PCa metastasis.